Mesh fixation devices and formation of intraperitoneal adhesions - ŞİRVANCI, SERAP (MARY ANN LIEBERT INC, 2006)
Purpose: To investigate the effect of mesh fixation devices on the formation of intra-abdominal adhesions. Materials and Methods: Fourteen New Zealand rabbits were used. In seven animals, nickel-titanium (nitinol) anchors (group 1) and titanium tacks (group 2) were applied by laparoscopy on the right and left sides of the abdomen, respectively. In the remaining seven rabbits, the same devices were applied on prosthetic meshes (groups 3 and 4, respectively). On day 30, the rabbits were sacrificed and macroscopic adhesion scoring was performed. All the specimens were assessed by scanning electron microscopy (SEM). Results: All parameters of adhesion except extension were significantly higher in group 4 than group 3 (P < 0.05). Comparisons of group 1 vs. group 2 were not statistically significant (P > 0.05). All the comparisons between a nonmesh group and a mesh group resulted in significant differences. SEM results revealed that the mesothelial cell layer and connective tissue intensively covered the tacks in group 2 whereas no similar findings were observed in group 1. Comparable appearances were encountered in groups 3 and 4. Conclusion: The nitinol anchor is associated with an acceptable level of adhesion formation and its intraperitoneal use can be considered safe in this regard.
Keywords: VENTRAL HERNIA REPAIR; PERITONEAL FIBRINOLYTIC-ACTIVITY; POLYPROPYLENE MESH; INCISIONAL HERNIA; LAPAROSCOPIC SURGERY; PORCINE MODEL; RECURRENCE; HERNIORRHAPHY; HERNIOPLASTY; PREVENTION